Pendampingan Hukum Konvergensi dalam Mengoptimalkan Masa Peka dan Tempo Perkembangan Santri di Daerah di Pondok Madrasah Tsanawiyah Zainul Hasan 1 Genggong - Abdur Rahman Vicki; Habibullah Habibullah; Endah Tri Wisudaningsih (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
This community service (PkM) was conducted to address problems related to the convergence law, sensitive periods, and developmental tempo among students (santri) at Madrasah Tsanawiyah Zainul Hasan 1 Genggong. The main issues included an imbalance in development (cognitive, emotional, social, and spiritual) due to fragmented learning approaches, missed stimulation during the sensitive periods, and a uniform approach that disregarded individual developmental tempo. The objective of this PkM was to provide an understanding of these concepts to both the students and the administrators, and to establish a more effective and adaptive learning approach. The methodology employed a qualitative approach with strategies such as participatory observation, in-depth interviews, and Focus Group Discussions (FGD), involving the Area D Administrators and students of Pondok MTs Zainul Hasan 1 Genggong. The results of the mentoring for Area D students demonstrated that their development became more balanced and integrated (convergence law), stimulation was provided during the appropriate sensitive periods, and mentoring was adjusted to the individual developmental tempo. These changes resulted in holistic progress, stronger skill formation among the students, and an increase in their learning motivation.